Learning and teaching in physical education - Hardy, Colin A.; Mawer, Mick. (London : Falmer Press, 1999)
Designed for BA, PGCE and ITE courses, this text brings together recent thinking together with research findings and examples of best practice in PE. It aims to cater for the growing pedagogical component of PE and sport science courses.
Includes bibliographical references and index.
Keywords: Physical education and training -- Study and teaching -- Great Britain; Physical education teachers -- Great Britain